The Fate of Labour Socialism : The Co-operative Commonwealth Federation and the Dream of a Working-Class Future - Naylor, James, 1954- (Book collections on Project MUSE., 2016)
"Almost a century before the New Democratic Party rode the first "orange wave," their predecessors imagined a movement that could rally Canadians against economic insecurity, win access to necessary services such as health care, and confront the threat of war. The party they built during the Great Depression, the Co-operative Commonwealth Federation (CCF), permanently transformed the country's politics. Past histories have described the CCF as social democrats guided by middle-class intellectuals, a party which shied away from labour radicalism and communist agitation. James Naylor's assiduous research tells a very different story: a CCF created by working-class activists steeped in Marxist ideology who sought to create a movement that would be both loyal to its socialist principles and appealing to the wider electorate. The Fate of Labour Socialism is a fundamental reexamination of the CCF and Canadian working-class politics in the 1930s, one that will help historians better understand Canada's political, intellectual, and labour history."--